Potential use of macroalgae Gracilaria gracilis in diets for European seabass (Dicentrarchus labrax): Health benefits from a sustainable source. Issue 119 (December 2021) - Passos, Ricardo; Correia, Ana Patrícia; Pires, Damiana; Pires, Pedro; Ferreira, Inês; Simões, Marco; do Carmo, Beatriz; Santos, Paulo; Pombo, Ana; Afonso, Clélia; Baptista, Teresa
Abstract: Seaweeds still possess a large undisclosed potential, mainly due to their constituent's richness, which may have several uses for society. In aquaculture, they may play a role as an ecological sustainable aquafeed supplement to increase overall health and fight pathogenic outbreaks. This study aimed to evaluate the general health modulation that the inclusion of Gracilaria gracilis could accomplish in the diet of Dicentrarchus labrax . Dried algae at 2.5% and 5% and algal extract at 0.35% inclusion levels were supplemented to seabass diet to evaluate possible growth, haematological, immunological, antioxidant, metabolic, and intestinal morphological modulations. The supplementations did not impact growth or feed utilization, and barely affected the haematological profile and some metabolic parameters. Nevertheless, it caused a marked outcome on lysozyme, some oxidative stress biomarkers, and intestine morphology, suggesting beneficial consequences from the algal inclusion. Dried algae powder, with a 2.5% inclusion, boosted immune response, with higher plasmatic lysozyme and intestinal acid goblet cells and protected against oxidative damages by improved enzymatic and non-enzymatic responses. Thus, we provide evidence that dietary seaweed application may be a path towards a more sustainable aquaculture industry. Highlights: Gracilaria gracilis in different percentages of supplementation plays distinct immunostimulant roles in Dicentrarchus labrax . Oxidative stress is reduced in fish when the seaweed is provided as a 2.5% supplement. Intestinal morphology and health may be modulated by G. gracilis supplementation. Not all percentages of inclusion or ways of employment of the supplement are equally suitable for the fish diet.